Theoretical and Practical Reason in Economics Capacities and Capabilities - Crespo, Ricardo F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The aim of the book is to argue for the restoration of theoretical and practical reason to economics. It presents Nancy Cartwright and Amartya Sen$1 (Bs ideas as cases of this restoration and sees Aristotle as an influence on their thought. It looks at how we can use these ideas to develop a valuable understanding of practical reason for solving concrete problems in science and society. Cartwright$1 (Bs capacities are real causes of events. Sen$1 (Bs capabilities are the human person$1 (Bs freedoms or possibilities. They relate these concepts to Aristotelian concepts. This suggests that these concepts can be combined. Sen$1 (Bs capabilities are Cartwright$1 (Bs capacities in the human realm; capabilities are real causes of events in economic life. Institutions allow us to deliberate on and guide our decisions about capabilities, through the use of practical reason. Institutions thus embody practical reason and infuse certain predictability into economic action. The book presents a case study: the UNDP$1 (Bs HDI.s
Table of contents -- Summary -- Preface -- Chapter I: Introduction -- Chapter II: Nancy Cartwright, Capacities and Nomological Machines: The Role of Theoretical Reason in Science -- Chapter III: Sen$1 (Bs Capability Approach: The Role of Practical Reason in Social Science -- Chapter IV: The Contributions of Aristotle$1 (Bs Thought to the Capability Approach -- Chapter V: Socio-Economic Machines and Practical Models of Development: The Role of the Human Development Index -- Chapter VI: Conclusion: Theoretical and Practical Reason in Economics.s
Keywords: Economics; Genetic epistemology; Ethics; Economics -- Methodology; Social sciences -- Methodology; Economics/Management Science; Methodology and the History of Economic Thought; Ethics; Methodology of the Social Sciences; Epistemology